PENGARUH DISPERSANT TERHADAP NANOPARTIKEL TiO2 SEBAGAI OPTIMASI DIRT-FREE PAINT - Adiati, Rima Fitria; Nurfadilah, Nurfadilah; Febiola, Cindy Claudia; Taufan, Ibnu; Fadhilah, Nur (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2014)
Research has been conducted to determine the effect of variations of dispersant on TiO2 nanoparticles as optimization of dirt-free paint. Dispersant used are Ethylene Glycol, Polyethylene Glycol, and Triton X-100 dissolved in white paint. Self-cleaning test with two kinds of stains shows that for mud stain, the best sample is the sample with Ethylene Glycol dispersant, by reduction of stain area reach 40.99 cm2. As for the food coloring stain, TiO2 samples with dispersant Triton X-100 with 24.57 cm2. SEM-EDX test results show that the TiO2 average particle size of paint without dispersant is 132.02 nm. By the addition of PEG, particle size becomes 104.98 nm. From the test results in this study can be shown that the dispersant material effect on the stability of a photocatalyst that can lead to self-cleaning properties, as well as agglomeration so it is able to disperse the TiO2 particles in the paint well.Â Keywords: Â dirt-free paint, dispersant, TiO2